Electrolarynx Voice Recognition Utilizing Pulse Coupled Neural Network - Arifin, Fatchul; Sardjono, Tri Arief; Purnomo, Mauridhy Hery (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2010)
The laryngectomies patient has no ability to speak normally because their vocal chords have been removed. The easiest option for the patient to speak again is by using electrolarynx speech. This tool is placed on the lower chin. Vibration of the neck while speaking is used to produce sound. Meanwhile, the technology of